THE IMPORTANCE OF THE TOY LIBRARY IN HEALTH PROMOTION AND IN THE PROCESS OF CHILD DEVELOPMENT (REMUNOM, 2023)
The act of playing is an instrument of great importance in the process of human development. Boys and games are capable of providing joy, pleasure, relaxation and favoring interaction between the child and their social reality. In this interaction, the child interacts with objects and with people. All this contributes to the construction of their social identity, as well as favors their cognitive development. The toy library, then, appears as an instrument capable of making available to the child and those responsible for it, as a strategic resource with several resources aimed at child development. By interacting with different toys and games, the child is able to represent their social reality in a more pleasant way, which facilitates the acquisition of various knowledge and the development of skills and abilities necessary for human beings. This study aims to investigate the contributions that toys and games can provide to children throughout their development, taking into account the use of toy library resources in different social spaces in which the child may be inserted. For this, an exploratory and qualitative bibliographic research was carried out, considering the contributions and theoretical contributions of renowned authors in the literature relevant to the subject of study. It is concluded by emphasizing that the toy library is a resource of vital importance for child care, considering that childhood is a very important stage for human development. In addition, it conceives the need to use the toy library as a strategy that must be part of every moment of the child's experience, in different contexts and social spaces.